The Magnetic Memory Effect of Ferromagnetic Materials in the Process of Stress-Magnetism Coupling - Guoqing Wang; Ping Yan; Liwa Wei; Zilong Deng (Advances in Materials Science and Engineering)
Ferromagnetic materials can produce the magnetic memory effect under stress. This provides a practical method to measure stress concentration. The relation between stress and magnetic characteristic is analyzed through energy balance theory. Force-magnetism coupling process of Fe-C crystal system is simulated by CASTEP software which is based on first principle. Electron band structure, electron density of states, and atomic magnetic moment in the process of force-magnetism coupling process are calculated. Experimental investigation of the magnetic memory effect of ferromagnetic material under different stresses has been undertaken in X52 pipeline. The results show that the magnetic characteristic of ferromagnetic material weakens under stress, and the magnetic memory signals intensity linearly decreases with the increasing stress. When material yields, the variation character of magnetic memory signals suddenly changes and the inflection points of the stress-B curves emerge. Experimental investigation is in agreement with the theoretical analysis.